Liquid chromatographic–tandem mass spectrometry assay for the quantification of MDT‐637 in human nasal wash. (21st May 2018) - Karnik, Shane C.; Cook, Robert; Gorman, Steve H.; Bakhtiar, Ray
Abstract: MDT‐637 is a new chemical entity that shows potent and selective antiviral activity against respiratory syncytial virus. As part of the new drug development program, a method for quantitating MDT‐637 in nasal wash collected from human subjects was required. This article describes the method development and validation and application of a bioanalytical assay for MDT‐637 in human nasal wash using liquid chromatography–tandem mass spectrometry. Sample pretreatment utilized supported liquid extraction and final extracts were injected onto an Agilent Poroshell 120 EC‐C18 column and eluted under isocratic conditions of 65:35 ( v /v) 10 mm ammonium formate in water and acetonitrile Detection was performed on an API 5000 tandem mass spectrometer operating in negative electrospray ionization mode applying multiple reaction monitoring. The assay was validated in accordance with the US Food and Drug Administration guidance on bioanalytical method validation and was applied in support of a Phase IIa human safety and tolerability study.